2006
DOI: 10.1007/s00402-006-0241-3
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral rotational knee instability: role of posterolateral structures

Abstract: The results of the current study confirm the concept that the rupture of the ACL is associated with ALRI. Current reconstruction techniques should focus on restoring the anterolateral rotational knee instability to the intact knee. Additional injury to the LCL further increases the anterior rotational instability significantly, while the PC is less important. Cautions should be taken when examining a patient with ACL rupture to diagnose injuries to the primary restraints of tibial rotation such as the LCL. If … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 45 publications
2
53
0
4
Order By: Relevance
“…Recently, Zantop [41] has underlined that antero-lateral rotational instabilities could increase tibial translation on ACL-deficient knees; therefore, the lateral plasty could be a valid solution in these combined and often underestimated lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zantop [41] has underlined that antero-lateral rotational instabilities could increase tibial translation on ACL-deficient knees; therefore, the lateral plasty could be a valid solution in these combined and often underestimated lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral patellofemoral ligament, popliteus tendon, popliteofibular ligament, and fabellofibular ligament have all been described in detail [3,[9][10][11][12][13]], but to date descriptions of the attachments of the LCL remain incomplete in the published literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, there has been increasing interest in extra-articular procedures because biomechanical studies have shown that additional injury to the lateral capsular structures increases anterior rotational instability significantly (Diermann et al 2009;Zantop et al 2007b).…”
Section: Extra-articular Stabilization Techniquesmentioning
confidence: 99%